PODSE: A computer program for optimal design of trials with discrete-time survival endpoints - Jóźwiak, Katarzyna; Moerbeek, Mirjam (Computer methods and programs in biomedicine, 2013)
► We created program for discrete-time survival endpoints. ► Good and optimal design of a trial can be found. ► Statistical power and cost of a trial design can be calculated. In experimental settings, one or more groups of subjects receive a treatment and they are compared to a group of subjects that receives a standard treatment or no treatment at all. These compared groups might have an equal number of subjects or some of the groups might have more participants relative to the other groups. Moreover, subjects in these groups can be followed over a short or a long period. To conduct experiments in a sufficient way, researchers should find a good design in the planning phase of the trial. The optimal design for experimental studies on event occurrence with discrete-time survival endpoints where two treatment groups are followed over time, is an optimal combination of the number of time periods, the total number of participants in the trial and the proportion of subjects in the experimental group. It is easy to find the best design for such studies using the PODSE program.